32. ASSESSMENT OF CHANGES IN FOLLICLE-STIMULATING HORMONE, LUTEINIZING HORMONE, PROLACTIN CONCENTRATIONS IN FEMALE PATIENTS WITH SEVERE ACNE VULGARIS TREATMENT WITH ISOTRETINOIN (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the effects of isotretinoin on FSH, LH, and prolactin hormone levels in female patients with severe acne vulgaris. Research subjects and methods: Clinical trial, prospective, comparing results before and after 3 months of treating severe acne vulgaris with isotretinoin 20 mg/day on 45 female patients at the National Dermatology Hospital from October 2022 to September 2023. Results: Before treatment, the rate of change in FSH, LH and prolactin levels was 6,7%; 8,9%; 13,3%, after treatment this rate of change tends to decrease to 6,7%; 4,4%; 2,2%. Although this change is not statistically significant with P>0,05, when evaluating the average concentration of hormones, it is found that: FSH decreased from 5,4±1,8 mIU/mL to 5±1,6 mIU/mL, P =0,03; LH decreased from 8±3,3 mIU/mL to 7,6±2,9 mIU/mL, P=0,04; prolactin decreased from 384,6±167,2 mIU/mL to 347,8±133,9 mIU/mL, P
Keywords: Acne vulgaris, FSH, GAGS, isotretinoin, LH, prolactin.